Exploring the roles of budget in Micro Small Medium Enterprises Indonesia - Septian Bayu Kristanto (Jurnal Penelitian Akuntansi (JPA), 2022)
We exploring the role of budget in Micro Small Medium Enterprises (MSMEs) in Indonesia. MSMEs face higher operating uncertainty because of the constraints of budget resources. We used field interviews to know the roles of budget in MSMEs. We used MSMEs engaged in Organic Green & Healthy (OGH) community. OGH community consists of farmers, artisans, and entrepreneurs of local MSMEs which produce organic and natural products. We find that budget development in MSMEs is tend to use a collaborative approach. MSMEs applies the loose use of budget for control purpose. The operational uncertainty in MSMEs leads this finding that small business is not to focus using the budget as a control function. MSMEs that linking budget and reward systems help small businesses to create an accurate budget. This study is the first evaluating budget development and uses using MSMEs in Indonesia